Sistem Temu Kembali Informasi Pasal-Pasal KUHP (Kitab Undang-Undang Hukum Pidana) Berbasis Android Menggunakan Metode Synonym Recognition dan Cosine Similarity - Safier Yusuf; Mochammad Ali Fauzi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Kitab Undang-undang Hukum Pidana (KUHP) is a matter that must be studied and even memorized for people engaged in their field, such as police, law enforcement officials, judges, lawyers or persons associated with the trial. KUHP is a book in which it consists of dozens of chapters and hundreds of chapters with a total of 569 articles, so that with a thick book it will become very inefficient and practical if it must be brought and also if you want to find related chapters that must open the page one by one manual. Based on these conditions in this study developed applications using synonym recognition and cosine similarity methods. Synonym recognition is a technique used to recognize words with different writing but has the same meaning. The cosine similarity method is used to calculate the similarity or closeness of the chapter documents with the query. The performance of the system is indicated by the results of the tests on each threshold variation of 5, 10 and 15, with optimal performance is at threshold 15 which has f.measure value of 0.404.